Confrontation clause after Crawford and its impact on the admissibility of forensic evidence: A comparative study on the United States and China - Xingyi Wang (Wolters Kluwer Medknow Publications, 2018)
Crawford is a watershed case separating hearsay exceptions and confrontation. Overruling Roberts, Crawford established a new bright-line test for Confrontation Clause. Testimonial out-of-court statements, whether reliable or not, are inadmissible unless the prosecution has shown: (a) the declarant is unavailable and (b) the defense has a prior opportunity for cross-examination. Applying Crawford's primary purpose test, testimonial out-of-court forensic reports (usually as affidavits) might not be admissible. However, Crawford underlined that the Confrontation Clause has its independent procedural values and other nonepistemic functions.